Facing the digital abyss: Media-Education and cultural mediations - Monica Fantin; Gilka Elvira Ponzi Girardello (Universidade Federal de Santa Catarina, 2010)
This article discusses digital inclusion from the perspective of education and culture, highlighting the ways the question is presented in Brazil, but understandin tha they are not exclusive to this context Given the complex challenges for digital conclusion in the context of globalization, the article emphasizes the importance that children and youth have real opportunities to use new technologies and languages, understanding that inclusion means much moe than acces to technologies, and is one of the fronts in the struggle against inequality. The authors propose that the understanding of the digital barrier be enriched  through the valorization of cultural mediations. The pa per discusses the possibilities for a culturalist perspective of media-education and promotes digital inclusion that is an experience of citizenship, belonging and critical and creative participation in the culture.